Growth of Entrepreneurial Opportunities: GEM Slovenia 2017, Executive Summary - Rebernik, Miroslav; Tominc, Polona; Crnogaj, Katja; Bradač Hojnik, Barbara; Rus, Matej (University of Maribor Press, 2018)
The scientific monograph comprises results of the Slovenian part of the largest global research project on entrepreneurship Global Entrepreneurship Monitor – GEM, which has completed its 19th cycle in 2017. GEM was established in order to (1) measure the differences regarding the relationship towards entrepreneurship, activities and aspirations of individuals in as many countries as possible, (2) uncover factors that encourage or hinder entrepreneurial activities, especially related to societal values, personal attributes and the entrepreneurship ecosystem, (3) provide a platform for assessing the extent to which entrepreneurial activity influences economic growth within individual economies and (4) uncover policy measures for the purpose of enhancing entrepreneurial capacity in an economy. The research helps to better understand the attitude of the society towards entrepreneurship and individual capabilities, among which are the perception of their own abilities for entrepreneurial activities, the ability to perceive opportunities, entrepreneurial intentions and fear of failure. As GEM monitors entrepreneurial activity throughout the phases of the life cycle (nascent, new businesses and established businesses, discontinuation), according to impact (high growth, innovation, internationalization) and by type (early-stage entrepreneurship activity, employee entrepreneurship activity), the picture is much richer than the one that is based only on data gathered from ordinary statistical databases.